PENGARUH SELEKSI DAN PELATIHAN TERHADAP PERSEPSI KINERJA PEGAWAI, DENGAN KOMPETENSI SEBAGAI VARIABEL INTERVENING (Studi Empirik Pada Inspektorat Jenderal Kementerian Agama) - Ali Ghozi; Darwanto . (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2017)
This study aims to verify and explain that Selection (X1) and Training (X2) has positive and significant influence to Perception of Employee Performance (Y2) mediated by Competency (Y1). Population in this study are employees at Inspectorate General of Ministry of Religion Affair. The sampel used in study are 136 respondents used sensus method. Data analysis was conducted by using Structural Equation Modeling (SEM) to analyze correlation between the independent variables (Selection (X1) and Training (X2) on the dependent variables (Perception of Employee Performance (Y2)) with Competency (Y1) as a intervening variable. The data was processed using AMOS 21.0 (Analysis of Moment Structures). The SEM analysis result has fulfilled Goodness of Fit Index Criteria with coefficient Chi-Square=36,078, Probability=0,171, RMSEA=0,043, GFI=0,953, AGFI=0,912, CMIN/df=1,244, TLI=0,956, and CFI=0,972. The result shows that selection has a positive and significant influence on the perception of employee performance (coefficient 0,65). Selection with competency as an intervening variable gives positive and significant influence on the perception of employee performance (coefficient 0,6878). Training has not a positive and significant influence on the perception of employee performance (coefficient -0,21). Training with competency as an intervening variable gives positive and significant influence on the perception of employee performance (coefficient 0,0798). Competency has a positive and significant influence on the perception of employee performance (coefficient 1,261). Keywords: selection, training, competency, perception of employee performance